Compliance of pregnant women in consuming FE tablets with anemia - Tio Simaremare; Kesaktian Manurung; Mido Ester J. Sitorus; Donal Nababan; Frida Lina Tarigan (Institute of Computer Science (IOCS), 2023)
According to the 2018 Riskesdas, data for pregnant women with anemia in Indonesia is 48.9% and in North Tapanuli it is 53.3%. The research aims to find out the Factors Affecting the Mothers' Adherence in Consuming Fe Tablet Medicine and Its Correlation to Anemia Incidents in Mothers in Pohantonga Village, Siborongborong Sub-District, Regency of North Tapanuli in 2022. This quantitative research employs Cross Sectional design with a population consisting of 42 pregnant mothers. Samples are taken using the total sampling technique and variables of the research are knowledge, attitude, family supports, access to health services, and mothers' adherence. The data obtained are analyzed using univariate and bivariate analysis. Bivariate analysis is conducted using the Chi-Square test and the result of the Chi-Square test indicates that knowledge, attitude, family supports, and access to health services are factors affecting mothers' adherence in consuming Fe tablet medicine. Mothers' adherence is not the factor causing Anemia incidents to occur in pregnant mothers. It is expected that pregnant mothers enhance their knowledge through either electronic media or brochures related to Fe tablets in order to decrease the rate of Anemia incidents during pregnancy. In addition, it is expected that the family supports pregnant mothers by always reminding them to consume Fe tablets. The researcher would like to thank the head of the puskesmas and the respondents. The researcher hopes that the results of this study will be useful for pregnant women, namely to increase hemoglobin levels not only with iron but also by paying attention to the nutrition in the food eaten and future researchers.